Retracting Locking-Pin Mechanism That Allows Partial Prosthetic Socket Doffing during Sitting. Issue 2 (April 2018) - Goldstein, Mark D.; Cagle, John C.; Hafner, Brian J.; Allyn, Katheryn J.; Sanders, Joan E.
ABSTRACT: Introduction: The purpose of this research was to develop a retractable tethered pin system to facilitate partial doffing and redonning of prosthetic sockets with locking-pin suspension. Materials and Methods: The system included a tethered cord that extended from a retracting mechanism on the pylon through the shuttle lock to a clip at the bottom of the locking pin. The mechanism operated similarly to a seatbelt retractor, applying low-level tension unless the user made a rapid pull on the tether to lock the mechanism. Results: Evaluation tests on four people with limb loss demonstrated that users liked the retracting mechanism and its capability to facilitate partial doffing and redonning. However, participants reported that the clip used to connect the mechanism to the locking pin worsened initial donning and final doffing of the socket. Conclusions: Modifications to the retractable tethered pin system design may overcome limitations and result in an easy and effective accommodation technology for people with transtibial amputation.